(untitled) (Journal of International Studies, 2020)
Nepal is a tiny Himalayan state situated in the northern part of South Asia. A land locked country, it is bounded by China (autonomous region of Tibet) in the north, and India in the east, west and south. It occupies about 56000 sq. miles of land and its population is about thirty million. Geographically, the country may be divided into three parts Himalayan region, Hill areas (including Kathmandu Valley), and the Tarai (plain). Nepal was a monarchical country from the beginning of its history, but recently (2008), monarchy was abolished and now it is a republican state. Various ethnic groups reside in different parts of the country, and most of them have their own mother tongue. Nepali in Devanagari script is the official language, but all the languages spoken in the country as mother tongue are recognized as national language. Nepal is an independent state from the very beginning of its history, and it never came under the yoke of any foreign rule.